Initial Specimen Diversion Device® reduces blood culture contamination and vancomycin use in academic medical centre. (February 2022) - Nielsen, L.E.; Nguyen, K.; Wahl, C.K.; Huss, J.L.; Chang, D.; Ager, E.P.; Hamilton, L.
Summary: Background: In suspected bloodstream infections, accurate blood culture results are critical to timely diagnoses and appropriate antibiotic administration. Aim: An Initial Specimen Diversion Device®, Steripath® (Magnolia Medical Technologies, Seattle, WA, USA) was evaluated for efficacy in reducing blood culture contamination at Brooke Army Medical Center (6.8% six-month contamination rate prior to intervention) in a six-month quality improvement project. Methods: Blood cultures in the emergency department were collected using either Steripath or the standard method. Blood samples of 20 mL were cultured into an aerobic and anaerobic medium and incubated for five days using an automated microbial detection system immediately after collection. Positive bottles were Gram-stained and plated. Rapid molecular polymerase chain reaction identification was performed on all first positive bottles within a blood culture set for each admission or ED visit. Speciation was deduced during antimicrobial sensitivity testing using the Vitek-2 instrument. Findings: Seven out of 1016 (0.69%) contamination events occurred when using Steripath vs 53 out of 800 (6.6%) contamination events when using the standard method. Steripath use was associated with a 90% lower incidence of blood culture contamination vs the standard method. Post study, Steripath use was implemented as standard practice hospital-wide, and a retrospective data analysis attributed a 31.4% decrease in vancomycin days of therapy to Steripath adoption. Conclusion: Using Steripath significantly decreased blood culture contamination events for bacterial bloodstream infections compared to the standard method. Subsequent adoption of Steripath reduced overall vancomycin usage. With widescale implementation Steripath could bolster antibiotic stewardship, mitigating antibiotic resistance caused by unnecessary antibacterial treatments.